PENERAPAN METODE PROBLEM-BASED LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR MATEMATIKA SISWA - Ana Susana (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2015)
This study is a Classroom Action Research about the application of Problem Based Learning method to increase students’ mathematic learning achievement in Dimension subject three XI class of SMK 1 Kawung Surabaya. This study consists of two cycles i.e. cycle I and cycle II. Each cycle had four steps that consist of plan, action, observation, and reflection. The data that is collected are data of individual and classical minimum standard from pre test and post test and also observation data in students’ response of each cycle. Subject of this study is students XI class of SMK 1 Kawung Surabaya academic year 2012-2013 with 38 student. The purpose of this study is to know the increasing of students’ mathematic learning achievement in Dimension Three subject, and to know the students’ response in the learning that used Problem-Based Learning method. Data analysis technique that is used is descriptive analysis i.e. analysis model by comparing the average of its percentage. From data analysis result, it can be seen that there is an increasing of students’ minimum standard classically from cycle I to cycle II. In the pre test, the classical standard was 47,36%, in the post test of cycle I was 55,26%, and in the post test of cycle II was 97,73%. It was shown the students’ response of Problem Based Learning method in the cycle I could not be said high, because of the percentage was in medium criteria. While in cycle II, the percentage was 97,73%. It is shown in the cycle II, the students’ response of Problem Based Learning method was in high criteria. Based on this study, it can be concluded that Problem Based Learning method can increase the XI class students’ mathematic learning achievement of SMK Kawung 1 Surabaya. Keywords: Students’ learning achievement, Learning result, Problem Based Learning method